The Cosmic Evolution of the Supermassive Black Hole Population: A Hybrid Observed Accretion and Simulated Mergers Approach - Fan Zou; W. N. Brandt; Elena Gallo; Bin Luo; Qingling Ni; Yongquan Xue; Zhibo Yu (The Astrophysical Journal, 2024)
Supermassive black holes (SMBHs) can grow through both accretion and mergers. It is still unclear how SMBHs evolve under these two channels from high redshifts to the SMBH population we observe in the local Universe. Observations can directly constrain the accretion channel but cannot effectively constrain mergers yet, while cosmological simulations provide galaxy merger information but can hardly return accretion properties consistent with observations. In this work, we combine the observed accretion channel and the simulated merger channel, taking advantage of observations and cosmological simulations, to depict a realistic evolution pattern of the SMBH population. With this methodology, we can derive the scaling relation between the black hole mass ( M _BH ) and host-galaxy stellar mass ( M _⋆ ), and the local black hole mass function (BHMF). Our scaling relation is lower than those based on dynamically measured M _BH , supporting the claim that dynamically measured SMBH samples may be biased. We show that the scaling relation has little redshift evolution. The BHMF steadily increases from z = 4 to z = 1 and remains largely unchanged from z = 1 to z = 0. The overall SMBH growth is generally dominated by the accretion channel, with possible exceptions at high mass ( M _BH ≳ 10 ^8 M _⊙ or M _⋆ ≳ 10 ^11 M _⊙ ) and low redshift ( z ≲ 1). We also predict that around 25% of the total SMBH mass budget in the local Universe may be locked within long-lived, wandering SMBHs, and the wandering mass fraction and wandering SMBH counts increase with M _⋆ .